Sistem Pendukung Keputusan Seleksi Pemilihan Kepala Bagian Perum Damri Surabaya - Maslihah; Rafdani Mufid (Melek IT : Information Technology Journal, 2017)
The process of appointing candidates for head of the department at Perum DAMRI Surabaya still use the manual method. With the development of today's technology Perum DAMRI Surabaya needs a new method so that it can provide recommendations in choosing the head section. Based on the existing problems then the authors take the title "Decision Support System Selection Appointment of Candidate Head of Section of Perum DAMRI Surabaya". The collection methods undertaken in the preparation of this final project are field studies and literature studies. Field studies include interviews and live observations while studying the literature by seeking information from archives with existing problems. For the research method using waterfall, the design process of "Decision Support System of Selection of Candidate Head of Section of Perum DAMRI Surabaya" begins by analyzing the system that has been running in the company, then the process of identifying existing problems, and after identification process the researcher design " Section of Perum DAMRI Surabaya "with system development model such as context diagram, conceptual model (CDM), physical data model (PDM), to input design, process, output